Etude morphométrique géométrique par la technique des points homologues du poisson Diplodus sargus (Linnaeus, 1758) au niveau de quelques stations de la côte algérienne - BOUHADDA, Alaeddine (My University, 2019)
The aim of this work in a morphometric study based on a landmark analysis of the common sar Diplodus sargus sargus (Linnaeus, 1758). The sampling was carried out on 60 individuals of D. sargus sargus brought from three different fishing ports on the Algerian coast: Tipaza, Salamandre- Mostaganem and Oran harbors. Standard length (L), height (H) and thickness (E) were measured for each fish. Other parameters have been added such as H/L, E/L and E/H ratios for statistical and biometric analyzes. Then the fish were photographed in a profile view in order to realize the morpho-geometric study on heighten chosen landmarks. A Canonical Variances Analysis (CVA) was carried out in order to study the sexual dimorphism and the morphometric dissimilarity between the different populations of D. sargus sargus on the heighten landmarks. The results showed that there is a sexual dimorphism that could be due to the biological specificities of D. sargus sargus. In addition, morpho-geometric dissemilarity caused by allopatric speciation between the populations of the three zones Tipaza, Mostaganem and Oran was observed, separating each population into a distinct group. The morpho-géometric analysis using landmarks seems to be hopeful method in fish taxonomy and could replace the expensive and tedious phylogenetic studies. This technique can show aspects of fish morphology that classical taxonomy cannot unseal.
Keywords: Speciation; common sar; Algerian coast; morphometric divergence; dimorphism